The Raven's Coloured Progressive Matrices Test: a pilot study for the establishment of normative data for Xhosa-speaking primary school pupils in the Grahamstown region - Bass, Natalie Tanyia (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
The Raven's Coloured Progressive Matrices (CPM) test is used extensively across a wide variety of settings in South Africa, however more appropriate local normative data has yet to be established. The CPM is internationally recognised as a culture-fair test of nonverbal intelligence, designed for use with children between the ages of 5Â½ and 11Â½. This pilot study thus sought to establish normative data for this instrument for a population of Xhosa-speaking Primary School children in the peri-urban township area in the Grahamstown region. The booklet version of the test was used and it was administered in group format and according to an alternate method of test administration (using Xhosa instructions) developed by Vass in 1992. The final normative sample consisted of 197 male and 182 female Xhosa-speaking children in Grades Two to Seven (N=379). The results showed (1) a significant effect of age on test scores, where scores increased with age as expected; (2) a consistent tendency for males to outperform females was also noted, however small sample sizes precluded any categorical claims to this effect; (3) no significant effect of education on test scores was observed and finally; (4) and finally, it appeared that the norms generated for this study revealed a tendency to be lower than those obtained by Raven, Court and Raven (1990) during the standardisation of this instrument in the United Kingdom and America. The study concluded that (1) there is an urgent need for more appropriate South African normative data for this test; and (2) that when assessing African children from disadvantaged backgrounds, further research into the effects of cultural and socio-economic factors and gender on non-verbal intelligence (and on performance on this test in particular) is required.
Keywords: Raven's Progressive Matrices; Students -- South Africa -- Psychology; Educational tests and measurements -- South Africa; Intelligence levels -- South Africa; Students -- Psychology